The edge of galaxy formation III: the effects of warm dark matter on Milky Way satellites and field dwarfs - Macciò, Andrea V.; Frings, Jonas (Monthly notices of the Royal Astronomical Society, 2019)
Abstract. In this third paper of the series, we investigate the effects of warm dark matter (WDM) with a particle mass of $m_WDM=3\, keV$ on